The effects and reliability of the hydroxychloroquine-azithromycin combination on the cardiac conduction system in patients with coronavirus disease 2019 - Uğuz, Berat; Zengin, İsmet; Topal, Dursun; Coşar, Selvi; Tiryakioğlu, Selma; Yılmaztepe, Mustafa Adem (Journal of Surgery and Medicine, 2020)
Aim: The COVID-19 virus influenced the world since late 2019 and affected millions of people. Although there is no unambiguous evidence in the treatment of COVID-19, the combination of hydroxychloroquine and azithromycin entered the protocols globally to reduce virus replication and take advantage of its immunomodulatory effects. It has been stated that both drugs extend QTc. However, the frequency of QTc prolongation in combinational drug use, and its effect on the primary endpoint, as well as the predictive values of QTc prolongation are not clear. Methods: A total of 135 patients who received hydroxychloroquine, azithromycin, and oseltamivir for suspected / definitive COVID-19 with viral pneumonia were examined in this single-center, retrospective study, Results: The mean age was 55.6 (19.1) years, and 61 (45%) patients were female. According to the initial ECG values, the QTc1 value was 422.44 (35.72) ms, while the QTc2 value was 446.91 (36.71) ms (P<0.001). The ECG evaluation after medication use indicated that the number of patients with a QTc value >500 ms was 6 (4.4%). The number of patients with prolongation in QTc values >60 ms was 7 (5.1%). The frequency of prolongation in QTc was 26% in intensive care unit patients, and 2% in low-risk patients in the inpatient unit. An elevation in troponin values >14 ng/L and a low GFR are predictors for QTc prolongation. None of these patients developed malignant arrhythmia or sudden cardiac death. Conclusion: Hydroxychloroquine and azithromycin combinations used in COVID-19 patients cause a prolongation in the QTc. The incidence of prolongation in QTc varies according to the comorbid characteristics and clinical status of the patients. Before starting hydroxychloroquine and azithromycin, the risk factors and clinical status of the patients should be well evaluated.